2014
DOI: 10.4236/jep.2014.514137
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Population’s Resistance to Toxic Exposures as an Auxilliary Tool of Decreasing Environmental and Occupational Health Risks (a Self-Overview)

Abstract: Environment chemical pollution can be persistent, and even virtually irremovable. For some chemicals in the workplace environment reliably safe low exposure levels are technically unattainable or presumably nonexistent. As a supplement to decreasing harmful exposures to as low levels as possible, the "biological prophylaxis" aims at enhancing host's protective mechanisms. During over 30 years in animal experiments modeling isolated or combined chronic or subchronic exposures to silica, asbestos, monazite, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The general concept of such "biological prophylaxis" of different occupational and environmental intoxications, its theoretical premises and general principles along with numerous examples of their realization have been published by us over several decades repeatedly, including, in review articles. 109,110 Now we began to use this experience for trying to protect the organism against the impacts of nanometals.…”
mentioning
confidence: 99%
“…The general concept of such "biological prophylaxis" of different occupational and environmental intoxications, its theoretical premises and general principles along with numerous examples of their realization have been published by us over several decades repeatedly, including, in review articles. 109,110 Now we began to use this experience for trying to protect the organism against the impacts of nanometals.…”
mentioning
confidence: 99%
“…Although it has already been discussed by us in this Journal [80], we reckon it useful to be briefly presented here.…”
Section: Some Theoretical Premises Of Biological Protectionmentioning
confidence: 99%
“…Although our studies summarized by Katsnelson et al (2014a) demonstrated a high efficiency of the organism's defenses against such nanoparticles' impact, safe levels of the latter should be very low if possible at all, due to these particles' especially high toxicity and seemingly obligatory genotoxicity. Therefore we deemed worthwhile to try and enhance the natural resistance to their adverse health effects with the help of so called bio-protectors.…”
mentioning
confidence: 94%